Does the Choice of Spinal Interbody Fusion Approach Significantly Affect Adjacent Segment Mobility?. Issue 21 (1st November 2021) - Wangsawatwong, Piyanat; Sawa, Anna G.U.; Pereira, Bernardo de Andrada; Lehrman, Jennifer N.; Turner, Jay D.; Uribe, Juan S.; Kelly, Brian P.
Abstract : Study Design: Biomechanical study of range of motion (ROM) at the vertebral levels adjacent to the construct of posterior pedicle screw-rod fixation with different types of lumbar interbody fusion techniques (LIF). Objective: To investigate the differences in adjacent segment mobility among three types of LIF: lateral lumbar interbody fusion (LLIF), transforaminal lumbar interbody fusion (TLIF), and posterior lumbar interbody fusion (PLIF). Summary of Background Data: Previous studies have concluded that LLIF, TLIF, and PLIF with posterior pedicle screw-rod fixation (PSR) provide equivalent stability in cadaveric specimens and are comparable in fusion rate and functional outcome. However, long-term complications, such as adjacent segment degeneration associated with each type of interbody device, are currently unclear. Little is known about the biomechanical effects of interbody fusion technique on the mobility of adjacent segments. Methods: Normalized ROM data at the levels adjacent to L3–L4 PSR fixation with three different types of lumbar interbody fusion approaches (LLIF, TLIF, and PLIF) were analyzed. Intact (n = 21) and instrumented (n = 7 per group) L2–L5 cadaveric specimens were tested multidirectionally under pure moment loading (7.5 Nm). Analysis of variance of adjacent segment ROM among the groups was performed. Statistical significance was set at P  < 0.05. Results: Normalized ROM was significantly greater with PLIF than with LLIF in all directions at both proximal and distal adjacent segments ( P  ⩽ 0.02) except for axial rotation at the distal adjacent segment ( P  = 0.07). TLIF also had greater normalized ROM than LLIF during lateral bending at the proximal adjacent segment ( P  = 0.008) and during flexion, extension, and lateral bending at the distal adjacent segment ( P  ⩽ 0.03). Normalized ROM was not significantly different between PLIF and TLIF. Conclusion: The choice of lumbar interbody fusion approach influences adjacent segment motion in a cadaveric model. LLIF had the least adjacent segment motion. Level of Evidence: 3 Abstract : The differences in adjacent segment mobility were investigated among lateral lumbar interbody fusion (LLIF), transforaminal lumbar interbody fusion (TLIF), and posterior lumbar interbody fusion (PLIF) with their associated interbody devices. L2–L5 cadaveric spines (n = 21, seven specimens per group) with L3–L4 pedicle screw-rod (PSR)+LLIF, TLIF, or PLIF were tested using pure moment loads (7.5 Nm). LLIF had the least adjacent segment mobility.